2007
DOI: 10.1093/toxsci/kfm043
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Contact and Respiratory Sensitization Potential of Volatile Organic Compounds Generated by Simulated Indoor Air Chemistry

Abstract: Up to 60 million people working indoors experience symptoms such as eye, nose and throat irritation, headache, and fatigue. Investigations into these complaints have ascribed the effects to volatile organic compounds (VOCs) emitted from building materials, cleaning formulations, or other consumer products. New compounds can result when the VOCs react with hydroxyl or nitrate radicals or ozone present in indoor environments. Several oxygenated organic compounds, such as glyoxal, methylglyoxal, glycolaldehyde, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
89
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(93 citation statements)
references
References 36 publications
2
89
0
2
Order By: Relevance
“…The volatile products of ozone/skin-oil chemistry can be inhaled, while the less volatile oxidation products can remain on the skin. Some of the inhaled volatile products, especially the dicarbonyls, may be respiratory irritants (41)(42)(43). Some of the less volatile products may be skin irritants (14-16, 44, 45).…”
Section: Resultsmentioning
confidence: 99%
“…The volatile products of ozone/skin-oil chemistry can be inhaled, while the less volatile oxidation products can remain on the skin. Some of the inhaled volatile products, especially the dicarbonyls, may be respiratory irritants (41)(42)(43). Some of the less volatile products may be skin irritants (14-16, 44, 45).…”
Section: Resultsmentioning
confidence: 99%
“…In vitro experiments suggest that TOXICOLOGIC PATHOLOGY diacetyl can increase airway reactivity (Fedan et al 2006). Diacetyl is also a sensitizing agent (Anderson et al 2007;Roberts et al 1999), certainly a concern given the wheezing reported by workers. Although fixed airways obstruction is the most distinguishing pulmonary function change noted in severely affected workers, some workers have a reversible component to their disease (Akpinar-Elci et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Extensive toxicological research has indicated that chronic exposures to moderate air toxics concentrations can cause long-term cancer and non-cancer health effects. [1][2][3][4][5] Nonetheless, further epidemiological studies are needed to characterize effects from specific compounds and mixtures. 6 -9 The National Air Toxics Assessment (NATA) investigated national patterns in emissions, concentrations, exposures, and risks.…”
Section: Introductionmentioning
confidence: 99%